Book Review of "Solution-Focused Brief Therapy with Clients Managing Trauma" - Makowecki, Serena (Canadian Journal of Counselling and Psychotherapy, 2019)
Solution-Focused Brief Therapy with Clients Managing Trauma is an edited book written by authors with expertise in using solution-focused brief therapy (SFBT) with traumatized clients. The editors propose that SFBT is a well-founded and efficient modality to use within trauma informed treatment. The SFBT approach is not without its critics, however, and some cautions are outlined in this review. Overall, the authors provide a unique interpretation of how the underlying tenets of SFBT offer both the therapist and the client a hopeful and effective path toward managing various types of traumatic experiences. They also provide specific strength-based SFBT tools for clients.